AMINA WADUD MUHSIN DAN PEMIKIRANNYA TENTANG POLIGAMI - Khozainul Ulum (Al Hikmah: Jurnal Studi Keislaman, 2017)
Long before Islam came, the human race on this earth has known since the old system of polygamy. Abrahamic religions law allows polygamy, with evidence that some prophets did. Similarly, in the Arab society before Islam, polygamy is practiced without any limitation of the number of wives. When Islam came, the custom of polygamy is not immediately eliminated. Even so, that does not mean the rules of polygamy in Islam is exactly the same as the pre-Islamic Arab culture. Muslims make many changes. The most noticeable difference is the absence of restrictions on the number of wives and the conditions for polygamy. This is confirmed by the Qur'an Sura al-Nisa 'third paragraph. In understanding this verse, Muslim clerics and scholars of classical and modern different opinions related to polygamy. One of them was Amina Wadud Muhsin. For Amina Wadud, if you pay attention to detail to al-Nisa 'third paragraph, it can be understood that Islam is more likely on the concept of monogamous marriage of polygamy, given the conditions of justice can not be done by the husband to marry more than one.